Clarice Lispector e Katherine Mansfield: relações de poder no universo infantil - Carneiro, Sarah Maria Borges (2013)
The present paper aims to exam comparatively the short stories “Felicidade Clandestina”, “Preciosidade” and “Os desastres de Sofia”, from Clarice Lispector, and “A casa de bonecas”, “A pequena governanta” and “Aula de canto”, from Katherine Mansfield. The problem is concerned with the strategies developed by children and adults to move around the relations of power that are developed associated with childhood. Even though they belong to different historical and cultural contexts, the writers are similar because they point out the presence of children characters in their narratives. Working with the hypothesis that the tensions that connect the Idea of power and childhood and unstable, we intend to verify how the characters of the selected short stories move around the childhood universe, breaking up with the paradigm of child’s victimization.